PENGATURAN SANKSI PIDANA TERHADAP JURU PARKIR LIAR YANG MEMINTA BAYARAN TARIF PARKIR TIDAK WAJAR - Sahira, Qintara; Rahmadan, Davit; Andrikasmi, Sukamariko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
A legal problem that often occurs in parking operations is the practice ofillegal parking attendants who charge unreasonable parking fees. Currently, theexistence of illegal parking attendants who charge unreasonable parking fees isincreasing in Indonesia, while there are no regulations that can catchperpetrators of these illegal fees. The aim of this skipsi research is firstly, to findout the reasons why it is important to regulate criminal sanctions against illegalparking attendants who charge unreasonable parking rates. Second, to formulatearrangements for criminal sanctions against illegal parking attendants who askfor unreasonable parking fees in the future.The type of research used is normative legal research using librarymaterials as data and reference sources. This research requires secondary dataconsisting of primary, secondary and tertiary legal material. The data collectiontechnique used by researchers is library research. This research uses a qualitativeanalysis method by interpreting legal materials. In drawing conclusions,researchers use a deductive method, namely drawing conclusions from generalstatements or propositions to specific statements or propositions.Based on the results of the research and discussion, there are two mainthings that can be concluded. First, the importance of regulating criminalsanctions against illegal parking attendants who charge unreasonable parkingrates aims to eradicate the practice of illegal fees in parking operations. Criminalsanctions are expected to be able to prevent the practices of illegal parkingattendants who charge unreasonable parking rates and provide a deterrent effectso that the perpetrator does not repeat the crime again. Second, the formula forregulating criminal sanctions against illegal parking attendants who ask forunreasonable parking fees in the future is in the form of criminal sanctions, finesand action sanctions in the form of job training.Keyword: Regulations-Criminal Sanctions-Illegal Levies-Parking Fees